Edição anotada e estudo das narrativas históricas de Alexandre Herculano situadas entre 1367 a 1433. - Santos, Débora de Lima (2016)
This thesis proposes a annotated edition and a study of the historical narratives of Alexandre Herculano located between 1367-1433, Arras forum for Spain, The vault, and Castle of Faria in this period include the reign of Ferdinand and D . John I. Such narratives were published at the beginning of the Portuguese Romanticism initially in journals of Portuguese journals then were gathered in volumes with other historical narratives of the author, and published under the title Legends and Lore. This research was developed from concern over the lack of this material in our academic context, it is noteworthy that other works of Herculaneum are much more affordable and therefore more known and studied, for example, the novels The Fool ( 1843), Eurico the priest (1844), and the Monk Cistercian (1848). This annotated edition proposal, we intend school player, college player, even the lay reader in general. Therefore, we intend to put the scope of this public an issue with notes to assist them while reading these stories, to have an enriched text with relevant information to clarify and enable a better understanding of it. Keywords: Historical Narratives; Annotated Edition; Alexandre Herculano.